Onde superficiali - Toraldo di Francia, G. (Giuliano) 1916-2011 (C.I.M.E. summer schools, 2011)
G. Toraldo di Francia: Premessa.-C.M. Angulo: A discontinuity problem on surface waves: The excitation of a grounded dieletric slab by a waveguide.- C.J. Bouwkamp: Notes on the conference.- H. Bremmer: Electromagnetic wave propagation around the earth.- L.B. Felsen: Asymptotic evaluation of integrals.- L.B. Felsen: Alternative Green's function representations for a grounded dielectric slab.- G. Gerosa: Propagation of electromagnetic waves in rectangular guides loaded with magnetized ferrite.- D. Graffi: Sulle condizioni al contorno approssimate nell´elettromagnetismo.- M.A. Miller, V.I. Talanov: The use of the surfaces impedante concept in the theory of electromagnetic surface waves.- S. Spitz: Note on continuous coupling of surface waves.- F.J. Zucker: Electroomagnetic boundary waves